2013
DOI: 10.1590/s1413-294x2013000100018
|View full text |Cite
|
Sign up to set email alerts
|

Relation between sleep and visuospatial skills in students from a public school

Abstract: The relation between the sleep and the visuospatial skills was evaluated in 31 students from a public school. For the analysis of sleep, the parents of volunteers answered a sleep evaluation questionnaire and the sleep diary. The visuospatial performance was evaluated by Wechsler Intelligence Scale for Children (WISC-III), through the subtest Picture Completion, the Perceptual Organization Index and the Performance IQ Scale. In accordance with the results, 72% of the students presented regular sleep and good s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Araújo et al [64] did not generally find an association between onset IIV and children’s visuospatial IQ scores. Similarly, Suratt et al [44] did not find an association between duration IIV and children’s scores on an intelligence subtest measuring visual-construction skills, but did find greater duration IIV to be associated with poorer performance on subtests measuring word knowledge and verbal reasoning.…”
Section: Resultsmentioning
confidence: 99%
“…Araújo et al [64] did not generally find an association between onset IIV and children’s visuospatial IQ scores. Similarly, Suratt et al [44] did not find an association between duration IIV and children’s scores on an intelligence subtest measuring visual-construction skills, but did find greater duration IIV to be associated with poorer performance on subtests measuring word knowledge and verbal reasoning.…”
Section: Resultsmentioning
confidence: 99%
“…For example, binocular depth inversion can be enhanced by sleep deprivation (Schmeider et al, 1996). Araujo et al (2013) examined the relationship between visual performance and hours of sleep in public school students. They found that going to sleep early and having a regular sleep schedule contributed to superior visuospatial performance.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that shorter sleep durations were associated with lower visuospatial abilities and with worse performance on visual-motor integration tasks. Araujo et al (2013) [4] examined the relationship between performance of visual perception and sleep time in public school students. They revealed that going to sleep early and having a regular sleep schedule contributed to better performance on visuospatial tasks.…”
Section: Introductionmentioning
confidence: 99%